Profile of a Forgotten Capital : Murshidabad in the Eighteenth Century - Chaudhury, Sushil, (Brill | Manohar Publishers & Distributors, 2018)
The role of Murshidabad, the capital of Bengal in the eighteenth century, in the political, social and economic life of the province is now almost lost to public memory. But the history of Murshidabad during the period is indeed a saga of romantic as well as tragic events which is unique. It's a pity that most works on Murshidabad, though commendable, were written a long time back. No doubt, quite a few excellent books and articles on the subject were published in the last several decades but unfortunately they deal with only certain aspects, and were not comprehensive histories of Murshidabad. So it was imperative to write a book covering all the aspects of the former capital. Here the author has tried to narrate an authentic history of Murshidabad with the help of evidence, both qualitative and quantitative, collected from various archives and libraries in Europe and India for more than four decades. He establishes in the book that it was the time of the Nawabi regime in the first half of the eighteenth century when Bengal witnessed its 'golden age'. He also explains critically and elaborately the activities of the three merchant-princes, and gives a new interpretation of the reasons behind the Plassey conspiracy and the subsequent revolution. The volume comes up with interesting facts about the Begums of Murshidabad, and finally, makes a critical analysis of Murshidabad's trade, industry, and economy on the one hand, and the society, culture and architecture on the other - all of which makes it a significant contribution on the subject.